2017
DOI: 10.1186/s40852-017-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

The business model prism: managing and innovating business models of arts and cultural organisations

Abstract: Purpose: This paper introduces and analyses the Business Model Prism (BMP) for the arts and cultural organizations as multidimensional framework to map the "as is" structure and the logic of their business model as well as to drive the design of innovation initiatives, i.e. the "as should be" business model. The framework can be used both for descriptive and normative purposes and comprises seven facets organized and represented with a tri-dimensional prism which defines the key business components of arts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
(33 reference statements)
0
39
0
Order By: Relevance
“…Hypothesis H3 is also accepted. This implies that the higher the service quality and efficiency of the bank, the higher the customer's satisfaction with the bank [49][50][51][52]. Note: p-value followed by * and ** are significant levels of 5% and 1%, respectively.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Hypothesis H3 is also accepted. This implies that the higher the service quality and efficiency of the bank, the higher the customer's satisfaction with the bank [49][50][51][52]. Note: p-value followed by * and ** are significant levels of 5% and 1%, respectively.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…For instance, the current research that found a relationship between fashion trendsetting and pro-environmental behaviors can be linked to emerging research topics, including how architectural trendsetters create imaginative architectural knowledge [67] or how trendsetters in various fields affect the dynamics from open innovation to evolutionary change [68]. Further research can also explore how business trendsetters develop novel business models for arts and cultural organizations [69], and how educational trendsetters can lead in creating innovative educational curriculum [70]. This interdisciplinary approach is expected to integrate knowledge frames among various fields such as fashion diffusion model, trendsetting model, open innovation principles, and architectural literacy.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…To do this, it is necessary to manage the life cycle of the product by considering the trade-off between assortment and efficiency. In particular, these issues are clearly seen in low-sales stores and small-size stores, so it is necessary to focus on these stores in order to improve the efficiency of the entire enterprise [32,33].…”
Section: Discussionmentioning
confidence: 99%